‘An Infinitude of Possible Worlds’: Towards a Research Method for Hypertext Fiction. - Jordan, Spencer (New Writing: The International Journal for the Practice & Theory of Creative Writing, 2014)
While the investigation of creative writing as a research method is gathering apace, little work has been done into the specific case of hypertext fiction (fiction written through a digital medium). This paper argues that, while there remain certain similarities between paper-based and digital texts, fundamental differences in design and construction remain. If hypertext fictions are to be successfully understood, then the role and purpose of the digital writer needs to be more fully analysed as part of the creative process. This paper argues that Possible Worlds Theory offers a way forward. With its focus on the ontological structures created by hypertext fiction, Possible World Theory actively embraces narrative indeterminacy and ontological changeability. In this sense the method provides a structured means by which the creative manipulation of the unique affordances of a digital medium by a writer can be theorised.